2019
DOI: 10.1021/acs.analchem.9b02554
|View full text |Cite
|
Sign up to set email alerts
|

Uracil-Mediated New Photospacer-Adjacent Motif of Cas12a To Realize Visualized DNA Detection at the Single-Copy Level Free from Contamination

Abstract: The CRISPR/Cas12a (cpf1) system was reported to indiscriminately cleave single-stranded DNA after binding with target DNA strands. This usually required the target DNA strands to contain the protospacer-adjacent motif (PAM) sequence of TTTN. Herein, we found Cas12a can also recognize another PAM sequence of UUUN resulting in activation of its ssDNA collateral cleavage effect. To make this finding useful, by combining with LAMP, we first realized CRISPR/Cas12a for directly visualized DNA detection at the single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…As an alternative to matching the temperatures of amplification and sensing, one can physically separate both reactions. To enable one-pot CRISPR reactions dehydrated CRISPR may for example be attached to the lid of a reaction tube for enhanced temperature stability ( Wu et al, 2020b ) ( Qian et al, 2019 ). Wu et al showed in 2020 their design of a lid where the Cas12a solution was separated from the reaction solution by a sealed film ( Wu et al, 2020a ).…”
Section: Challenges In Poc Crispr Sensing Systemsmentioning
confidence: 99%
“…As an alternative to matching the temperatures of amplification and sensing, one can physically separate both reactions. To enable one-pot CRISPR reactions dehydrated CRISPR may for example be attached to the lid of a reaction tube for enhanced temperature stability ( Wu et al, 2020b ) ( Qian et al, 2019 ). Wu et al showed in 2020 their design of a lid where the Cas12a solution was separated from the reaction solution by a sealed film ( Wu et al, 2020a ).…”
Section: Challenges In Poc Crispr Sensing Systemsmentioning
confidence: 99%
“…With its ability to accurately recognize specific sequence, the CRISPR/Cas system holds promise as a detection method (Huang et al, 2018;Sashital, 2018;Li et al, 2019). The transcleavage activity of the recently reported Cas12a, Cas13a, and Cas14 systems in particular, helps them first bind to the target specifically and then amplify the binding signal by cutting the dual-labeled probe in a nonspecific way (Gootenberg et al, 2017;Chen et al, 2018;Harrington et al, 2018;Qian et al, 2019). New nucleic acid detection technologies for different purposes using the CRISPR/Cas12a and Cas13a systems, such as DETECTR, SHERLOCK and HOLMES etc., have extremely high sensitivities and specificities (single base resolution), and have been developed in combination with other gene amplification methods, including PCR and RPA (Gootenberg et al, 2017Chen et al, 2018;Myhrvold et al, 2018;Santos et al, 2018;Shan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…By a LAMP assay, genetic targets can be amplified up to 10 9 copies within 1 h. The Cas12a biosensor based on LAMP technology can realize simple, specific, efficient and economical detection of target. For example, Wang et al [29] reported that Cas12a can also recognize the PAM sequence of UUUN instead of TTTN. They capitalized on this finding by combining with uracil-DNA-glycosylase (UDG) enzymes, which have the ability to degrade uracil contained in contaminated dsDNA templates, with uracil-LAMP, to design a supersensitive DNA sensing platform: UDG and LAMP and CRISPR (ULC).…”
Section: Nucleic Acid Detectionmentioning
confidence: 99%
“…Therefore, Cas12a has recently been widely expanded as a diagnostic tool for detecting nucleic acids with high sensitivity in vitro [11,25] . To achieve fluorescent detection of low‐abundance nucleic acid targets, it is often necessary to combine some nucleic acid amplification strategies, including polymerase chain reaction (PCR), [23,26] recombinase polymerase amplification (RPA), [9b,c,10a,c,d,f,12,32] loop‐mediated isothermal amplification (LAMP), [10b,e,27,29,33] enhanced strand displacement amplification (E‐SDA), [34] rolling circle amplification (RCA), [35] or catalytic hairpin assembly (CHA) [28] (Table 1).…”
Section: The Application Of Crispr‐cas12a In Biosensingmentioning
confidence: 99%